National Health Interview Survey, 1992: Cancer Control Supplement ([Verlag nicht ermittelbar], 1994)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The 1992 Cancer Control Supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1992 [ICPSR 6343]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Variables unique to this supplement include items on acculturation (e.g., language, ethnic identification, place of birth of self and parents), medical care, food knowledge, cancer knowledge and attitudes, cancer screening knowledge and practice, smoking and other tobacco use, and occupational exposures to harmful substances.